2011
DOI: 10.1007/s11357-011-9290-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in 100-km ultra-marathon running performance

Abstract: The aims of this study were (1) to investigate the participation and performance trends at the '100 km Lauf Biel' in Switzerland from 1998 to 2010, and (2) to compare the age-related changes in 100-km running performance between males and females. For both sexes, the percent of finishers significantly (P<0.01) decreased for the 18-29 and the 30-39-year age groups, while it significantly (P<0.01) increased for the 40-49 and the 50-59-year age groups over the studied period. From 1998 to 2010, the mean age of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
201
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(221 citation statements)
references
References 57 publications
18
201
1
1
Order By: Relevance
“…The age of Olympic gold medal winners in the men's 100m dash was at ~23 years between 1896 and 1980. Similar results were found for other distances as for short and middle distance running [4], half-marathon running [19], marathon running [20] and ultra-marathon running [21]. In other endurance sports disciplines such as Ironman triathlon, the age of peak swimming speed increased in the swim split across years [22].…”
Section: Introductionsupporting
confidence: 79%
“…The age of Olympic gold medal winners in the men's 100m dash was at ~23 years between 1896 and 1980. Similar results were found for other distances as for short and middle distance running [4], half-marathon running [19], marathon running [20] and ultra-marathon running [21]. In other endurance sports disciplines such as Ironman triathlon, the age of peak swimming speed increased in the swim split across years [22].…”
Section: Introductionsupporting
confidence: 79%
“…Second, Hunter et al (2011) indicated that men and women physiologically peaked at a similar age in marathon running performance. The maximal performance of the top five runners in the World Marathon Majors Series and in the International Athletic Association Federation World Championship was obtained at~30 years of age for both sexes, while older runners (from 30 to 54 years) obtain the best race times in 100-km competitions (Knechtle et al 2012). In the present study, we have found that maximal performance in the marathon is earlier than previously believed since peak performance was obtained at 27 years in men and at 29 years in women.…”
Section: Discussionmentioning
confidence: 97%
“…Age-related declines in endurance and ultra-endurance performance have been well described in the literature for running [24,35,38,54,83,89,90,91] , cycling [92,93,94,95] , swimming [83,85] and more recently, for triathlon. [34,79,92,96,97,98] Endurance and ultra-endurance performance appears to be maintained until approximately 35-40 years of age, followed by modest decreases until 50 years of age and a progressive decrease in performance thereafter.…”
Section: Age-related Declines In Triathlon Performancementioning
confidence: 89%
“…[24,25,35,90] A relative increase in participation of masters triathletes has also been observed during the past decade for short and long distance triathlon, while the participation of triathletes younger than 40 yrs of age has decreased. [27,28,30,58] The relative increase in participation of master triathletes at the Ironman distance triathlons has been accompanied by an improvement in their performance.…”
Section: Improvements In Triathlon Performance Of Elderly Triathletesmentioning
confidence: 95%